Peran dan Fungsi Bahasa dalam Kehidupan Manusia di Era Industri 4.0 dan Abad 21 - Miranda Ade Tias Putri Riyanto; Silvina Noviyanti; Maryana Tambunan (Departement of Mathematics Education, 2024)
The purpose of writing this article is to show the importance of language in everyday life. As social creatures, humans cannot live alone and definitely need the help of other people. Language facilitates easier communication between individuals. In the context of everyday life, Indonesian has a very significant role as a unifier of meaning. The differences in language and culture that exist in Indonesian society can be united through Indonesian. The method used in this research is the library method, which involves studying various sources such as journals, articles and books that are relevant to the research topic regarding the role and function of language in human life in the industrial era 4.0 and the 21st century.